(untitled) (Ágora Journal, 2024)
This study aims to analyze aspects of race and labor relations involving the watermen of Feira de Santana/BA, between 1893 and 1936. We used documents such as codes of bylaws, registration books, newspaper articles and photographs to access fragments of the experiences of the water workers in a context of urban land redevelopment, based on practices of racialization and policeization of street workers. The post-abolition period appears as an important reading key, helping to understand the different positions taken by black workers and local elites with regard to the use and appropriation of urban territory.